Profile of Students’ Misconception Levels on Newton’s Laws Using a Six-Tier Diagnostic Test - Hafsah Huwaida Az Zahra Yahya; Fuji Hernawati Kusumah; Erina Hertanti (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Conceptual understanding is a fundamental foundation in physics learning; however, numerous studies have reported that students continue to hold misconceptions that are resistant to formal instruction. One topic that is particularly prone to misconceptions is Newton’s Laws, which serve as a basis for understanding more advanced physics concepts. This study aims to profile students’ levels of misconceptions on Newton’s Laws based on diagnostic results obtained using a six-tier diagnostic test. This research employed a quantitative descriptive approach with a survey design. The participants were 132 eleventh-grade students from SMAN 2 Cikampek, selected through purposive sampling. The instrument used was a six-tier diagnostic test covering three sub-concepts of Newton’s Laws and analyzed based on combinations of students’ answers, conceptual reasoning, confidence levels, and sources of reasoning. The results indicate that although the sound understanding category showed the highest percentage (43.99%), more than half of the students were still classified as having problematic understanding, particularly misconceptions and negative errors. Misconceptions were consistently identified across all three sub-concepts of Newton’s Laws with a cumulative pattern, where the highest level of misconception occurred in Newton’s Third Law, especially in understanding action–reaction force pairs. From the perspective of misconception sources, students’ misconceptions were predominantly derived from internal cognitive constructions based on intuition and everyday experiences. These findings emphasize that instruction on Newton’s Laws should focus on eliciting and reconstructing students’ prior conceptual understanding in an integrated manner, so that persistent misconceptions can be reduced and students’ conceptual understanding can be improved.